1977
DOI: 10.1115/1.3446275
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Diffusion of Momentum and Mass of Fuel in a Diesel Fuel Spray

Abstract: An investigation on the diesel fuel spray injected into stagnant ambient air in a chamber is reported in this paper. The objective of the investigation was to analyze the processes of diffusion of mass and velocity of the fuel in the fuel spray. The distribution of velocity and mass of the fuel showed similarity in the zone of established flow. Gaussian normal probability distribution for free jet was assumed by earlier workers, starting with Albertson, et al., for analyzing such a situation. However, it has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
4
1
1
Order By: Relevance
“…The final zone (beyond ~3.5 mm) shows a good agreement with the results given by the theoretical model for a Sc value near 0.5. This value is lower than those observed by Prasad and Kar (1976), but it must be considered that their study was developed under quite different conditions (P in < 20 MPa, ϕ o > 0.4 mm, P back = 0.1 MPa). Furthermore, they found that Sc decreased as injection pressure got higher, which would imply that values lower than 0.7 could be expected under modern engine conditions, as it has been obtained in the current study.…”
contrasting
confidence: 57%
See 3 more Smart Citations
“…The final zone (beyond ~3.5 mm) shows a good agreement with the results given by the theoretical model for a Sc value near 0.5. This value is lower than those observed by Prasad and Kar (1976), but it must be considered that their study was developed under quite different conditions (P in < 20 MPa, ϕ o > 0.4 mm, P back = 0.1 MPa). Furthermore, they found that Sc decreased as injection pressure got higher, which would imply that values lower than 0.7 could be expected under modern engine conditions, as it has been obtained in the current study.…”
contrasting
confidence: 57%
“…Some authors use gas jet distributions as a first approximation. Experimental similarities between them have been always remarked by other researchers (Adler and Lyn 1969;Prasad and Kar 1976;Sinnamon et al 1980;Correas 1998;Desantes et al 2006a). Different expressions for radial profiles can be found in the literature (Abramovich 1963;Hinze 1975;Schlichting 1978;Spalding 1979;Sinnamon et al 1980).…”
Section: Theoretical Derivationmentioning
confidence: 57%
See 2 more Smart Citations
“…Existen diferentes expresiones en la literatura que modelan el perfil radial de velocidad de un chorro diésel [47,105,112,119]. Desantes et al [29] hicieron un estudio comparativo de estos perfiles, llegando a la conclusión de que el que mostraba un mejor comportamiento a la hora de reproducir las características del chorro diésel es el perfil gaussiano propuesto anteriormente por Correas [22]:…”
Section: Distribución De Velocidad Y Concentraciónunclassified